Bone turnover in pregnancy, measured by urinary CTX, is influenced by vitamin D supplementation and is associated with maternal bone health: findings from the Maternal Vitamin D Osteoporosis Study (MAVIDOS) trial - Curtis, EM; Parsons, C; Maslin, K; D'Angelo, S; Moon, RJ; Crozier, SR; Gossiel, F; Bishop, NJ; Kennedy, SH; Papageorghiou, AT; Fraser, R; Gandhi, SV; et al. (Oxford University Press, 2021)
Background The pattern of change in maternal bone turnover throughout pregnancy is poorly characterized.